2023
DOI: 10.3390/nu15020359
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Adherence to the Mediterranean Diet with Depression in Older Adults Longitudinally Taking into Account Cognitive Status: Results from the HELIAD Study

Abstract: Although research has generally shown a negative association between depression and adherence to the Mediterranean diet (MeDi), the literature related to older adults is controversial, perhaps partially due to the fact that cognitive status has not been considered. The aim of the current work was to investigate the association between MeDi and incident depression in a representative cohort of people, taking into account their cognitive status in multiple ways. The sample was drawn from the HELIAD study, a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…In a recent umbrella review reporting the association between seven dietary patterns and depression ( Gianfredi et al, 2023 ), the authors concluded that there is compelling or suggestive evidence for an inverse association between the Mediterranean diet, a dietary pattern based on vegetables and fruits, fish, grains and beans, and olive oil, and depression. The Hellenic Longitudinal Investigation of Aging and Diet study from Greece showed that after adjusting for age, gender, education, and baseline cognitive status, those in the highest quartile had a 46 % lower risk of depression compared to older adults with the lowest adherence to the Mediterranean diet (hazard ratio = 0.549; 95 % CI: 0.359 to 0.840) ( Mamalaki et al, 2023 ). We also noted that the lack of statistical-level associations between the first quartile of HEI and depressive symptoms may be explained by insufficient covariates adjusted for, and an important factor is physical activity, which has been shown to be strongly associated with the risk of depression ( Laird et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent umbrella review reporting the association between seven dietary patterns and depression ( Gianfredi et al, 2023 ), the authors concluded that there is compelling or suggestive evidence for an inverse association between the Mediterranean diet, a dietary pattern based on vegetables and fruits, fish, grains and beans, and olive oil, and depression. The Hellenic Longitudinal Investigation of Aging and Diet study from Greece showed that after adjusting for age, gender, education, and baseline cognitive status, those in the highest quartile had a 46 % lower risk of depression compared to older adults with the lowest adherence to the Mediterranean diet (hazard ratio = 0.549; 95 % CI: 0.359 to 0.840) ( Mamalaki et al, 2023 ). We also noted that the lack of statistical-level associations between the first quartile of HEI and depressive symptoms may be explained by insufficient covariates adjusted for, and an important factor is physical activity, which has been shown to be strongly associated with the risk of depression ( Laird et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hodge et al (13) ( n 8660, aged 50–69 years) showed that MD was associated with less psychological distress, with the OR in the highest scoring group relative to the lowest scoring group being 0·72 (95 % CI = 0·54, 0·95). A very recent study carried out in Greece (Mamalaki et al ) (15) , including 879 participants aged 65 years and older without depression at baseline, showed that each unit increase in MD score was associated with a 6·2 % decrease in the risk of depression. Although Skarupsi et al (14) and the studies by Hodge (13) and Mamalaki (15) reported an inverse association between high adherence to MD and depressive symptoms in older people, they did not consider stratification by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity, for example, has been shown to promote synaptic growth and reduce inflammation, thus protecting the brain against oxidative stress and neurodegeneration [ 19 ]. Other lifestyle modifications, including diet, sleep hygiene, mindfulness, and meditation, have been proposed to benefit the brain against depression, cognitive decline, and neurodegeneration [ 117 , 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%